ADDITION OF DIFFERENT GALANGAL PERCENTAGES AGAINST THE ORGANOLEPTIC VALUE OF SHREDDED DRIED SALTED GOURAMI (Trichogaster trichopterus) - Purnomo Purnomo; Iin Khusnul Khotimah; Irwan Irwan; Juhana Suhanda; Rabiatul Adawyah (Fish Scientiae, 2022)
The State of Indonesia has a fairly large archipelago of potential fish resources (6,520,100 tons/year), as stated in the Decree of the Minister of Marine Affairs and Fisheries number KEP.45/MEN/2011 seen from the potential of Indonesia's marine resources. According to Article 1 of Law 45 of 2009, fish are all kinds of living things which all or part of their life cycle is in the aquatic environment.The purpose of this study was to obtain the best percentage of galangal for shredded dried salted fish in Sepat Swamp. The benefits of this research are to optimize the utilization of salted salted fish (Trichogaster trichpterus) to increase public consumption, to increase the selling value of salted fish (Trichogaster trichopterus), to increase the diversification of processed products from dried salted fish.This study used an experimental method with 4 treatments, namely: treatment O = 0% galangal from the weight of fish meat, treatment A = 5% galangal from the weight of fish meat, treatment B = 10% galangal from the weight of fish meat and treatment C = 15% galangal from the weight of the fish. fish weight. Organoleptic testing used moderately trained panelists, selected from students of Fishery Products Technology, Faculty of Fisheries and Marine Affairs, Lambung Mangkurat University. After the panelists assessed the dried salted fish shredded product, the data analysis was continued using the sign test. The test uses organoleptic test with description method. Based on organoleptic test with descriptive test that the addition of galangal has a significant effect on the shredded dried marsh sepat fish. the organoleptic test results of dried sepat swamp salted fish shredded with the addition of galangal with the best formulation on the addition of the percentage of galangal in treatment C with 15% galangal. Specifications Appearance 7.05, Aroma 8.6, Taste 8.6 and Texture 8.1